Effects of 1,4-dihydropyridine derivatives (cerebrocrast, gammapyrone, glutapyrone, and diethone) on mitochondrial bioenergetics and oxidative stress: a comparative study - Fernandes, Maria A. S. (2003)
The potential protective action of 1,4-dihydropyridine derivatives (cerebrocrast, gammapyrone, glutapyrone, and diethone) against oxidative stress was assessed on mitochondrial bioenergetics, inner membrane anion channel (IMAC), Ca2+-induced opening of the permeability transition pore (PTP), and oxidative damage induced by the oxidant pair adenosine diphosphate (ADP)/Fe2+ (lipid peroxidation) of mitochondria isolated from rat liver. By using succinate as the respiratory substrate, respiratory control ratio (RCR), ADP to oxygen ratio (ADP/O), state 3, state 4, and uncoupled respiration rates were not significantly affected by gammapyrone, glutapyrone, and diethone concentrations up to 100 [mu]M. Cerebrocrast at concentrations higher than 25 [mu]M depressed RCR, ADP/O, state 3, and uncoupled respiration rates, but increased three times state 4 respiration rate. The transmembrane potential ([Delta][Psi]) and the phosphate carrier rate were also decreased. At concentrations lower than 25 [mu]M, cerebrocrast inhibited the mitochondrial IMAC and partially prevented Ca2+-induced opening of the mitochondrial PTP, whereas gammapyrone, glutapyrone, and diethone were without effect. Cerebrocrast, gammapyrone, and glutapyrone concentrations up to 100 [mu]M did not affect ADP/Fe2+-induced lipid peroxidation of rat liver mitochondria, while very low diethone concentrations (up to 5 [mu]M) inhibited it in a dose-dependent manner, as measured by oxygen consumption and thiobarbituric acid reactive substances formation. Diethone also prevented [Delta][Psi] dissipation due to lipid peroxidation initiated by ADP/Fe2+. It can be concluded that: none of the compounds interfere with mitochondrial bioenergetics at concentrations lower than 25 [mu]M; cerebrocrast was the only compound that affected mitochondrial bioenergetics, but only for concentrations higher than 25 [mu]M; at concentrations that did not affect mitochondrial bioenergetics (<=25 [mu]M), only cerebrocrast inhibited the IMAC and partially prevented Ca2+-induced opening of the PTP; diethone was the only compound that expressed antioxidant activity at very low concentrations (<=5 [mu]M). Cerebrocrast acting as an inhibitor of the IMAC and diethone acting as an antioxidant could provide effective protective roles in preventing mitochondria from oxidative damage, favoring their therapeutic interest in the treatment of several pathological situations known to be associated with cellular oxidative stress.